The complete mitochondrial genome sequence and phylogenetic analysis of yellow weasel (Mustela sibirica) - Mengshi Yu; Huailiang Xu; Diyan Li; Jiayun Wu; Anxiang Wen; Meng Xie; Qin Wang; Guangxiang Zhu; Qingyong Ni; Mingwang Zhang; Yongfang Yao (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we determined the complete mitochondrial genome sequence of the Mustela sibirica. The complete mitogenome of M. sibirica is 16,529 bp in length and consist of 13 protein-coding genes (PCGs), 2 rRNA genes, 22 tRNA genes, and a D-loop region. The overall base composition of the mitochondrial DNA is 32.88%A, 13.84%G, 27.32%T, and 25.96%C. The phylogenetic tree of the family Mustelidae constructed by using mitogenome sequences from 10 mustelid species of the family Mustelidae. These results provide necessary information for molecular phylogeny and evolutionary analysis of the M. sibirica.